2013
DOI: 10.1097/qai.0b013e31829c6de0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of CD4+ T-Cell Immune Activation and Interleukin 10 Levels Among HIV, Hepatitis C Virus, and HIV/HCV-Coinfected Patients

Abstract: CD4 immune activation with HLA-DR⁺ expression in HIV/HCV coinfection with well-controlled HIV may arise from chronic HCV viremia. Conversely, CD4⁺CD38⁺ expression may be driven by underlying HIV infection. CD4 immune activation was unexpectedly found to be associated with decreased liver fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…Immune activation is a direct measure of disease progression, and earlier work has shown that CD38 expression on CD8+ T cells likely reflects the status of immune activation in viral‐infected individuals . Our current investigation clearly showed an increase in the expression of HLA‐DR and CD38 on T cells of HCV‐infected compared to HCs in line with recent findings , also confirming peripheral CIA.…”
Section: Discussionsupporting
confidence: 91%
“…Immune activation is a direct measure of disease progression, and earlier work has shown that CD38 expression on CD8+ T cells likely reflects the status of immune activation in viral‐infected individuals . Our current investigation clearly showed an increase in the expression of HLA‐DR and CD38 on T cells of HCV‐infected compared to HCs in line with recent findings , also confirming peripheral CIA.…”
Section: Discussionsupporting
confidence: 91%
“…[10,29] More recent studies have reported CD8 T-cell activation is not enhanced in HCV/HIV coinfected [11,24,30] and HCV/HIV coinfected subjects have activated CD4 T cells. [11,24] An earlier study in the WIHS cohort by Kovacs et al [29] reported elevated CD8 T-cell activation in HCV/HIV coinfected subjects, wherein HIV-1 disease in most women was at an early stage: almost 50% were untreated and only 7.7% were receiving HAART. In contrast, a more recent study in WIHS cohort by Kuniholm et al [24] assessing T-cell phenotype in HIV-infected women stratified by HCV RNA did not find CD8 T-cell activation in HCV/HIV coinfected women.…”
Section: Discussionmentioning
confidence: 99%
“…[8,9] Studies examining the effects of HCV co-infection on immune activation are contradictory with some reporting an association with CD8 T cell activation not confirmed in others. [10,11] HCV progression in HIV infection has been reported to be owing to HIV-mediated loss of CD4 helper T cells. [12] Liver damage in chronic infection is predominantly from non-HCV-specific inflammatory T cells infiltrating the liver.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, in coinfection, microbial products entering the blood should cause strong immune activation. Indeed, the level of immune activation in HIV/HCV coinfection is higher than that in HIV [144,145] or HCV [146,147] monoinfection alone.…”
Section: Detrimental Effects Of Hepatitis C On the Course Of Hiv Infementioning
confidence: 98%